Infectious diseases and climate change (Archives of Pediatrics of Uruguay, 2025)
Introduction: infectious diseases represent a significant threat to health, with many of them being climate-sensitive. The increase in global temperature, generated by human activities, causes variations in climate patterns and an increase in the frequency of extreme meteorological events. All of this determines important and serious impacts on health.Objectives: to raise awareness among physicians and healthcare workers about the impact of climate change on health, with a particular focus on its effects on infectious diseases.Methodology: a review of the scientific evidence (systematic reviews) published in the last 5 years in PubMed on climate change and infectious diseases was carried out. A table was created for data extraction, where the following were recorded: title, author, year and place of publication, objective, period of studies included in that review, and continent and/or countries, factor or disease considered, and results and/or conclusions.Results: 36 reviews were identified, 8 of which met the objective and were selected. The research works included countries in America, Africa, Asia, Oceania, and Europe. In all the reviews, the increase in temperature showed a strong correlation with infectious diseases, increasing their incidence. The diseases referred to were: diarrheal diseases (parasitic and bacterial), dengue, malaria, West Nile virus, leptospirosis, cutaneous leishmaniasis, and hand-foot-mouth disease. An increase in the distribution area of vector-borne diseases was also identified.Conclusions and comments: the systematic reviews, carried out in different countries and on different infectious diseases, conclude that climate change significantly influences the increase in the incidence and distribution thereof, and this trend is expected to continue. It is imperative that the health sector actively engage in environmental management practices to contribute to slowing down these changes, anticipate, adapt, mitigate their consequences, and consider these factors in the planning and development of health policies.
Keywords: Communicable Diseases; Climate Change; Global Warming